2011
DOI: 10.1016/j.jfe.2010.07.002
|View full text |Cite
|
Sign up to set email alerts
|

U.S. softwood lumber demand and supply estimation using cointegration in dynamic equations

Abstract: a b s t r a c tThis research estimated dynamic supply and demand equations for the U.S. softwood lumber using two-stage least squares. Long-run and ECM equations were derived from the estimated coefficients. Empirical data included monthly observations from 1990 to late 2006. Stationarity of the residuals was explored using Augmented Dickey-Fuller statistics. Results suggest that demand and supply elasticities in both short and long-run are relatively small compared with past studies. The Canadian softwood lum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 29 publications
3
13
0
Order By: Relevance
“…The United States has historically imported a substantial share (on average, 28% between 1979 and 2013) of softwood lumber domestically consumed. These imports and domestic production have been driven in part by softwood lumber demand from the construction sector (e.g., Song et al 2011). To quantify softwood lumber consumption, we formulate a reduced-form softwood lumber quantity equation that is derived from equilibrium supply and demand.…”
Section: Monte Carlo Projection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The United States has historically imported a substantial share (on average, 28% between 1979 and 2013) of softwood lumber domestically consumed. These imports and domestic production have been driven in part by softwood lumber demand from the construction sector (e.g., Song et al 2011). To quantify softwood lumber consumption, we formulate a reduced-form softwood lumber quantity equation that is derived from equilibrium supply and demand.…”
Section: Monte Carlo Projection Methodsmentioning
confidence: 99%
“…This provides an assessment of possible ranges of residential construction that would drive wood products demands under alternative assumptions about economic growth. Second, we incorporate it into a projection of potential ranges of softwood lumber consumption in the United States (e.g., Song et al 2011) over the same time span. Monte Carlo methods are used to generate median levels and probability bands for housing starts and softwood lumber consumption, given assumptions about economic growth, over these future decades.…”
mentioning
confidence: 99%
“…Song et al (2011) derive long run supply and demand equations using two-stage least squares using monthly data from 1990 to 2006, and estimate demand and supply elasticities in the U.S. lumber market. The Canadian export supply equation was derived from the Cobb-Douglas profit function and controlled for log-transformed price index in Canadian dollars received by Canadian sawmills exported to the U.S., U.S. market price of softwood lumber, Canadian to U.S. dollar exchange rate, tariff rate, prices of input factors, inventory of Canadian sawmills, dummy variables for the months when softwood lumber export from Canada to the U.S. was taxed under Memorandum of Understanding (MOU), dummy variable for months from October 1991 to February 1992 when the U.S. taxed imported softwood lumber from Canada based on the expired MOU, and another dummy variable for the months from April 1996 to March 2001 when the SLA was effective (Note 6).…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…Likewise, Lindsey et al (2000) and Zhang (2001Zhang ( , 2006 reached the same conclusion with respect to SLA 1996. Devadoss (2006), Mogus et al (2006), and Song et al (2011) found that CVDAD had significant negative impacts on Canadian lumber imports. Recently, Baek (2012), Nagubadi and Zhang (2013), and Parajuli and Zhang (2016) looked into the effects of SLA 2006 in its 7-9 years of operation on the U.S. lumber imports from Canada and found it to be effective.…”
Section: Introductionmentioning
confidence: 99%